2010
DOI: 10.1210/jc.2009-1492
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Components Worsen Lower Urinary Tract Symptoms in Women with Type 2 Diabetes

Abstract: Our results suggest that MS may especially influence LUTS and OAB in diabetic women, probably by compounding the effect of peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 35 publications
1
57
1
Order By: Relevance
“…This finding is plausible for many reasons. One, the association of LUTS with metabolic factors, including HDL, has been well-documented previously (Parsons et al, 2006(Parsons et al, , 2007Tai et al, 2010). It has been postulated that metabolic factors are involved in the pathogenesis of LUTS via vascular impairment, and consequent bladder hypoxia would impact the function of the bladder (McVary, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…This finding is plausible for many reasons. One, the association of LUTS with metabolic factors, including HDL, has been well-documented previously (Parsons et al, 2006(Parsons et al, , 2007Tai et al, 2010). It has been postulated that metabolic factors are involved in the pathogenesis of LUTS via vascular impairment, and consequent bladder hypoxia would impact the function of the bladder (McVary, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Tai et al . [16] also suggested that MS may especially influence LUTS and OAB in diabetic women, probably by compounding the effect of peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that compared with the nonMetS group, the MetS group reported significantly higher storage and total symptom scores and a borderline increase in voiding symptom. When individual symptoms were compared, the average score of urgency, nocturia, and intermittency was significantly higher in the MetS group (11). In an other study, a total of 2371 men (mean age 46.1 years) and 731 women (mean age 53.9 years) were analyzed.…”
Section: Discussionmentioning
confidence: 93%